2018
DOI: 10.31887/dcns.2018.20.1/phenningsen
|View full text |Cite
|
Sign up to set email alerts
|

Management of somatic symptom disorder

Abstract: This review paper gives an overview of the management of somatic symptom disorder. It starts with a description of the clinical problem of patients with persistent bodily distress, discusses classificatory, epidemiological, and etiological issues and then describes the evidence and practical principles of dealing with these patients who are often seen as “difficult” to treat. It is concluded that the best-suited approach is stepped care with close cooperation of primary care, a somatic specialist, and mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 51 publications
0
73
1
9
Order By: Relevance
“…Thus, the perception that the main task of the GP is to diagnose, treat and reassure the patient became a barrier to adequately managing PPS. Henningsen stated that good communication with the patients is essential at all stages of PPS and levels of care, including reassurance, anticipation of likely outcomes of diagnostic tests, positive explanations of the functional character of the disorder and motivation of the patient to actively engage in the coping with PPS [ 13 ]. However, our findings showed that PPS is often not communicated in the consultation, and management strategies are not properly addressed, leaving the patients to seek alternatives for symptom relief and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the perception that the main task of the GP is to diagnose, treat and reassure the patient became a barrier to adequately managing PPS. Henningsen stated that good communication with the patients is essential at all stages of PPS and levels of care, including reassurance, anticipation of likely outcomes of diagnostic tests, positive explanations of the functional character of the disorder and motivation of the patient to actively engage in the coping with PPS [ 13 ]. However, our findings showed that PPS is often not communicated in the consultation, and management strategies are not properly addressed, leaving the patients to seek alternatives for symptom relief and management.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients often found the GP to be inadequately prepared for the consultation, and they perceived the GP to be prejudiced [ 12 ]. In line with this, GPs often experience patients with PPS as burdensome and difficult to treat, and negative attitudes towards these patients are found among GPs [ 13 , 14 ]. GPs struggle with the incongruence between the patients’ persistent symptom presentations and the explanatory models for biomedical disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been only few evidences on treatments for SSD that several forms of psychotherapy showed low-to-moderate evidence for e cacy and there has been limited investigations of peripheral interventions. 35 These results of different involvement of brain regions according to organ symptoms suggest the further studies on peripheral interventions for speci c symptom, for example, vestibular rehabilitation for patients with dizziness. This study had several limitations.…”
Section: Discussionmentioning
confidence: 91%
“…This was then broken down into Fine and Gross motor, with gross motor being broken down into 2 further leaf categories. The last of the top level groupings was somatic, and this refers to those subjects associated with bodily responses [ 13 ]. Somatic was then broken down into 8 leaf categories.…”
Section: Methodsmentioning
confidence: 99%